KONSEP CORPORATE RESCUE DALAM KEPAILITAN DI INDONESIA - Sitompul, Natasya Aisyah (Faculty of Law, Tanjungpura University, 2021)
Abstract Corporate Rescue Concept goal is to save company from bankruptcy so its business can be continued and the debts can be paid. This concept has been applied in other countries. Researcher is interested conducting research concerning how the corporate Rescue concept applied in Indonesian bankruptcy act and attempted in bankruptcy practices in Indonesia, also how the urgency of Corporate Rescue concept is associated with the bankruptcy process in Indonesia. This study uses normative legal research method by analizing bankruptcy act, judges 'decisions and the reports of creditors' meetings in the bankruptcy process associated with the corporate rescue concept. Books, journals, and papers are also used as supporting data. The research results are described in descriptive analytical form as follow. The corporate rescue concept is implied in postponement of debt payment obligations provision of Indonesian bankruptcy act. The debtor is obliged to submit a reconciliation proposal regarding debt restructuring, one of the shape of corporate rescue concept. However, the act does not explain further information. Corporate rescue concept has also been implemented in the bankruptcy and postponement of debt payment obligations process. The Supervisory Judges, the curators/administrators always recommends that the Debtor should immediately prepares a reconciliation proposal to the creditors. However, the recommendation is only at the formality stage. The creditors' focus is how their receivables can be paid by liquidated debtor’s asset, therefore the reconciliation proposal has been rejected rather than approved. According to the Indonesian bankruptcy act, solvent companies and companies whose business line concerns basic human needs are easy to be bankrupted, if companies don’t pay debt which is due and collectible to one of their creditors. So to save them and the interests of concurrent creditors, corporation rescue concept must be adopted into Indonesian bankruptcy act and must be socialized to all stake holder. Abstrak Corporate Rescue Concept adalah suatu upaya untuk menyelamatkan perusahaan dari kepailitan agar usahanya tetap bisa berjalan dan utangnya kepada para kreditur dapat dibayar. Konsep sudah diterapkan di negara-negara lain. Peneliti tertarik untuk melakukan penelitian tentang bagaimana konsep Corporate Rescue diatur di dalam Undang Undang Kepailitan dan diupayakan dalam praktek kepailitan di Indonesia serta bagaimana urgensi Corporate Rescue dikaitkan dengan proses kepailitan di Indonesia. Penelitian ini menggunakan metode penelitian hukum normatif karena yang dianalis adalah data sekunder berupa undang-undang, putusan hakim dan laporan hasil rapat-rapat kreditur dalam proses kepailitan dikaitkan dengan konsep Corporate Rescue. Sebagai data dukung juga digunakan buku, jurnal dan paper, selanjutnya hasil penelitian diuraikan dalam bentuk deskriptif analitis. Konsep Corporate Rescue telah tersirat di dalam Undang Undang Kepailitan di Indonesia di dalam ketentuan tentang penundaan kewajiban pembayaran utang, karena tujuan dari Penundaan Kewajiban Pembayaran Utang (PKPU) adalah untuk merestrukturisasi utang debitur pada para krediturnya, namun restrukturisasi utang tidak diatur lebih lanjut di dalam Undang Undang Kepailitan atau ketentuan hukum lainnya. Konsep Corporate Rescue juga belum menjadi pola pikir hakim maupun Kurator/Pengurus dalam proses kepailitan maupun PKPU. Fokus para kreditur masih pada konsep likuidasi harta debitur agar piutang mereka dapat dibayar oleh debitur. Berdasarkan Undang Undang Kepailitan di Indonesia, perusahaan-perusahaan yang solvent dan perusahaan yang bergerak di bidang pemenuhan kebutuhan dasar manusia mudah untuk dipailitkan apabila perusahaan tersebut tidak membayar utang yang sudah jatuh tempo dan dapat ditagih pada salah satu krediturnya. Agar perusahaan tersebut dan para kreditur konkurennya dapat diselamatkan, dibutuhkan penerapan konsep Corporate Rescue, oleh karena itu konsep tersebut harus diadopsi ke dalam Undang Undang Kepailitan di Indonesia, dan harus disosialisasikan kepada hakim, kurator dan masyarakat, agar dapat dimengerti manfaat dari konsep tersebut.